EFFECT OF SMOKING ON HEART RATE VARIABILITY IN NORMAL HEALTHY VOLUNTEERS - Doss D, Samuel Sundar; S, Anandhalakshmi; K, Rekha; K, Akhil Antony (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The aim of this study is to determine the effect of tobacco smoke on heart rate variability (HRV). Methods: This study included 90 male smokers (30-mild, 30-moderate, 30-severe) (Group II) and 30 age-matched non-smokers as controls (Group I). HRV analysis was performed using 8 channels Physiopac of Medicaid Company. All the subjects were subjected to HRV test. The short-term 8 minutes HR recording was performed for HRV analysis. Results: Mean RR, mean HR, root mean square of the successive differences, of the smokers and non-smokers, did not differ significantly. However, smokers NN50, Pnn50, high frequency (HF) declined significantly, and the smokers show significantly higher low frequency (LF), LF/HF ratio when compared with those of the non-smoking individuals (p<0.05). Conclusion: HRV analysis of smokers and nonsmokers showed that smoking subjects had an autonomic imbalance suggestive of an increased sympathetic tone or decreased parasympathetic tone. Sympathetic overactivity may lead to cardiovascular disease development in smokers. Keywords: Smoking, Healthy volunteers, Heart rate variability.